STRATEGIC MANAGEMENT IN NONPROFIT AND PUBLIC ORGANIZATIONS - Ioan NICOLAE (Management & Marketing)
Strategic management in public organizations can use coerciveness as a keyelement of their strategy. Private organizations are more dependent onmarketing or selling to potential customers. As publicness increases,marketing declines in importance and maintaining favorable coercivearrangements increases in importance. Strategic managers should be awareof coercive opportunities in their mandates as they fashion strategy anddevise implementation plans.